2020
DOI: 10.1101/2020.11.16.385849
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TheRhinolophus affinisbat ACE2 and multiple animal orthologs are functional receptors for bat coronavirus RaTG13 and SARS-CoV-2

Abstract: Bat coronavirus (CoV) RaTG13 shares the highest genome sequence identity with SARS-CoV-2 among all known coronaviruses, and also uses human angiotensin converting enzyme 2 (hACE2) for virus entry. Thus, SARS-CoV-2 is thought to have originated from bat. However, whether SARS-CoV-2 emerged from bats directly or through an intermediate host remains elusive. Here, we found that Rhinolophus affinis bat ACE2 (RaACE2) is an entry receptor for both SARS-CoV-2 and RaTG13, although RaACE2 binding to the receptor bindin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…However, in a recent work it was shown that the ACE2 receptor of R. affinis bats can effectively bind and mediate the entry of both RaTG13 and SARS‐CoV‐2 viruses in a pseudovirus assay. [ 11 ] Therefore, the recombination may have occurred in cells of horseshoe bats. Notably, a high frequency of recombination events has been shown between SARS‐like bat coronaviruses presumably involved in the emergence of SARS‐CoV in 2002.…”
Section: Points Of Disagreement With the Segreto/deigin Hypothesismentioning
confidence: 99%
“…However, in a recent work it was shown that the ACE2 receptor of R. affinis bats can effectively bind and mediate the entry of both RaTG13 and SARS‐CoV‐2 viruses in a pseudovirus assay. [ 11 ] Therefore, the recombination may have occurred in cells of horseshoe bats. Notably, a high frequency of recombination events has been shown between SARS‐like bat coronaviruses presumably involved in the emergence of SARS‐CoV in 2002.…”
Section: Points Of Disagreement With the Segreto/deigin Hypothesismentioning
confidence: 99%
“…Such investigations would include testing wild animal hosts of coronaviruses at the nucleic acid and serum levels to positively identify the natural origin of the cross-species spillover. Various studies 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 have already reported that several species of mammals (including mink, civets, cats, pangolins, rabbits, ferrets, foxes, deer, etc) are capable of being infected by SARS-CoV-2. It is entirely possible that SARS-CoV-2-related viruses could cross the species barrier between humans and animals repeatedly in many parts of the world.…”
mentioning
confidence: 99%
“… 64 , 65 , 66 , 67 Moreover, Chinese scientists have conducted a series of research projects to investigate the origin of SARS-CoV-2 since the COVID-19 outbreak, and have made much progress in understanding epidemiology, infection mechanisms, and animal host searching. 30 , 34 , 35 , 68 , 69 …”
mentioning
confidence: 99%